Determination of Sustainability of MSMEs in Bandar Lampung City: The Role of Financial Literacy and Digital Payment - Aisya Putri Adha; Ersi Sisdianto; Okta Supriyaningsih (Journal of Islamic Economics and Finance, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy, it is important to verify the extent to which Financial Literacy and the use of Digital Payments can promote the Sustainability of  Micro, Small and Medium Enterprises in an increasingly competitive business environment. This study aims to analyze the influence of the two main variables Financial Literasy and Digital Payment on the Sustainability of Micro, Small and Medium Enterprises. Quantitative approach and Field research method  with a target of 100 samples of micro, small and medium enterprises were randomly selected using the Simple Random Sampling method. Data analysis was carried out using SmartPLS to measure the magnitude of the influence of each variable on business sustainability. The results of the study show that Financial Literacy and Digital Payment have a significant positive influence (p: 0.003, 0.000) on the sustainability of MSMEs, with medium to large effects (F²: 0.210, 0.288). This research model can explain the 55.5% variation in the sustainability of small and medium-sized enterprises (adjusted R² = 0.555). These results prove that increasing Financial Literacy and expanding the use of Digital Payment are the main factors that support the sustainability of  micro, small and medium enterprises in the Bandar Lampung area.